Multi-physics modelling of a grid connected diesel engine driven synchronous generator set for the analysis of transient low voltage ride through performance - Tweedy, Oliver (2021)
Understanding the electromechanical behaviour of synchronous generators during severe low voltage fault conditions is vital to measure the potential performance impact and damage that may occur as a result to both connected equipment and the generator set. The work outlined in this paper addresses the process of developing a multi-physics model of a grid connected synchronous generator utilising 2D transient electromagnetic modelling with co-simulation of a 1D torsional beam element model. A 3D finite element model of a synchronous generator rotor is created and analysed using the ANSYS modal solver to obtain the orthotropic elastic properties of the laminated generator rotor core using a parametric modal analysis technique. The first 8 modes are obtained with a mean error of 1.3%, proving the accuracy of the method as the first contribution to knowledge.